Measurement of corporate social responsibility (CSR) of a social enterprise in Singapore, NTUC FairPrice - Chia, Hui Ching (2014)
The popularisation of Corporate Social Responsibility (CSR) in today’s society has witnessed the resurgence of debates among literatures in understanding the concepts of CSR. This study will seek to understand CSR level of the Singapore Supermarket Industry while in tandem, analyse through an economic perspective using a framework of Private Benefits and External Benefits (or externalities).